Impact of culture-based bacteriological examination on diagnosis and treatment in cats with chronic nasal disease — Insights from a case series of 25 cats - Emming, Christin; Verspohl, Jutta; Beineke, Andreas; Rösch, Sarah (Frontiers in Veterinary Science, 2025)
IntroductionDiagnosing feline nasal cavity diseases typically involves computed tomography, rhinoscopy, mycological examination, and histopathology. Culture-based bacteriological examination (cBE) is frequently performed, though its diagnostic and therapeutic relevance remains uncertain. Chronic rhinosinusitis (CRS), a diagnosis of exclusion, often responds poorly to standard antibiotics. This retrospective case series aimed to describe the correlation of cBE findings (1) across nasal diseases and (2) treatment responses in CRS cases.MethodsMedical records of 25 cats with confirmed nasal disease using comprehensive diagnostics were reviewed.ResultsIncluded were 11 CRS cats, 7 with mycotic rhinitis, and 7 with nasal neoplasia. In 24/25 cats, cBE was positive, with similar bacterial isolates across all groups. In CRS cats, treatment response did not consistently correlate with cBE results or antimicrobial susceptibility. 5/11 CRS cats showed clinical improvement following a 21-day doxycycline course. The remaining 6/11 CRS cats had not responded to previous targeted antibiotic therapy or empirical doxycycline for potential Mycoplasma species infection. 3/6 cats responded only to immunosuppressive therapy notably cyclosporine in two CRS cats, representing the first report in feline medicine. Non-responders were 3/6 CRS cats with marked turbinate destruction; 2/3 tested positive for feline herpesvirus 1.ConclusionFor diagnosing nasal diseases, cBE showed limited diagnostic relevance. In CRS, observations suggest that cBE may have limited diagnostic and therapeutic utility, leading to a clinical dilemma in interpretation. Empirical doxycycline treatment and immunosuppressive strategies, including cyclosporine, may be beneficial in selected CRS cases. Given the limitations of cBE, PCR testing for Mycoplasma species and viral pathogens may improve clinical decision-making in cats with CRS, both by helping to identify potential candidates for doxycycline treatment, and by assessing the risk of viral reactivation prior to initiating immunosuppressive therapy.